2016
DOI: 10.1080/14787210.2017.1252260
|View full text |Cite
|
Sign up to set email alerts
|

A European survey of perendoscopic treatment of biliary complications in patients with alveolar echinococcosis

Abstract: European centers use perendoscopic biliary drainage as an efficient and safe alternative to surgery to treat AE biliary complications. Insertion of multiple plastic stents delays stent occlusion and leads to effective and prolonged bile duct patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 26 publications
0
19
0
1
Order By: Relevance
“…A European survey of perendoscopic procedures (through ERCP) to treat biliary complications of AE in 18 clinical centers showed that such procedures are now used routinely and are generally successful in alleviating symptoms and in maintaining long-term permeability of the biliary strictures; to achieve good results, extensive saline lavage of the bile ducts, which removes necrotic debris and intrahepatic biliary stones that are common in such patients, and the use of multiple plastic stents are recommended (211) (Fig. 6).…”
Section: Treatment Of Aementioning
confidence: 99%
See 1 more Smart Citation
“…A European survey of perendoscopic procedures (through ERCP) to treat biliary complications of AE in 18 clinical centers showed that such procedures are now used routinely and are generally successful in alleviating symptoms and in maintaining long-term permeability of the biliary strictures; to achieve good results, extensive saline lavage of the bile ducts, which removes necrotic debris and intrahepatic biliary stones that are common in such patients, and the use of multiple plastic stents are recommended (211) (Fig. 6).…”
Section: Treatment Of Aementioning
confidence: 99%
“…6). Although there have been no specific studies assessing the quality of life of patients receiving such treatment, we may anticipate that this has markedly contributed to the improved quality of life of those patients with chronic biliary obstruction and multiple cholangitis episodes; in the past, more than 10 reoperations in a single patient were not uncommon, and most patients had a very uncomfortable external biliary drainage tube for life (211).…”
Section: Treatment Of Aementioning
confidence: 99%
“…In AE, partial resection of AE lesions was commonly performed, associated with surgical biliary drainage, until retrospective analysis of cases from European teams showed that such interventions were followed by an increased rate of complications and decreased survival of the patients (Buttenschoen et al, 2009;Kadry et al, 2005). Palliative surgical interventions may be replaced by percutaneous or perendoscopic interventions of drainage and/or stenting, especially to alleviate complications of biliary obstruction or to treat bacterial infection of the central necrotic cavity in AE lesions (Ambregna et al, 2017;Vuitton et al, 2016). Whenever possible, any intervention should be associated with ABZ treatment: 1 to 3 months after any interventions for CE, 2 years after radical resection for AE.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Il est désormais possible de réaliser par voie endoscopique une désobstruction des canaux biliaires envahis par les lésions parasitaires, d'évacuer les débris qui transitent par ces canaux, et les calculs qui s'y sont formés, et de poser des stents en plastique pour rétablir leur perméabilité.P ourr estaurer définitivement cette perméabilité,lamise en place de plusieurs stents à la fois, disposés«en fagots » et la répétition de cette mise en place de stents, sont indispensables. C'est ce que vient de montrer une enquête rétrospective européenne initiéep ar le service de gastroentérologie-endoscopie digestived uC HU de Besançon qui révèle aussi que cette technique est désormais de pratique courante dans les centres européense n charge des patients atteints d'EA [44].…”
Section: L'endoscopie Biliaire Interventionnelle :I Ndiquéep Our Le Tunclassified